Additive manufacturing of Bio-inspired ceramic bone Scaffolds: Structural Design, mechanical properties and biocompatibility. (May 2022) - Jiao, Chen; Xie, Deqiao; He, Zhijing; Liang, Huixin; Shen, Lida; Yang, Youwen; Tian, Zongjun; Wu, Guofeng; Wang, Changjiang
Graphical abstract: Highlights: The design method based on Voronoi was proposed to mimic the characteristics of cancellous bone in human body. Ceramic Digital light processing (DLP) method was adopted to satisfy the forming requirements of irregular scaffolds. The compressive strength of scaffolds can be increased by 30% through the regulation of irregularity. Cell experiments confirmed that structural changes also had influence on the biocompatibility of scaffolds. Abstract: Ideal bone scaffolds require good biocompatibility and moderate mechanical properties, so as to promote the proliferation and differentiation of osteoblast cells, and achieve the good bone repair. Inspired by the porous structure of cancellous bone, 15 groups of bone scaffolds with variable irregularity (Ir1-5) and porosity (35.53–61.75%) were designed and fabricated by ceramic digital light processing (DLP) using 20 wt% hydroxyapatite doped zirconia as the matrix material. The effects of structural parameters and material on mechanical properties and biocompatibility were studied. The shrinkage test results showed that the density of scaffolds was mainly affected by the porosity. The mechanical test results showed that Ir2 and Ir3 scaffolds had better compressive behaviors, and the compressive strength could be increased by 30% by regulating the irregularity. All scaffolds showed comparable mechanical properties to that of cancellous bone. Cell experiments showed that the effect of structure on cell proliferation, differentiation, and mineralization was most evident at the early stage of implantation. Meanwhile, the biocompatibility variation with the irregularity was consistent with mechanical properties. This study proved that a bio-inspired bone scaffold with excellent comprehensive properties could be obtained through reasonable design.